Morphological, Anatomical and Palynological Investigation of Plantago cordata Lam. (Plantaginaceae) from Pakistan - Bahadar, Khalida; Zaynab, Madiha; Noman, Ali; Fatima, Mahapara (PSM Biological Research, 2018)
Plantago cordata Lam. (Plantaginaceae) collected from Hazara was investigated by its, morphology, leaf epidermis anatomy and pollen grain morphology. It is a threatened herb, having thickened elongated roots, heart shaped leaves with long petioles. Leaf epidermis anatomy and pollen grain morphology have been examined by the light microscope. Morphological and anatomical examination revealed that the test plant had double walled upper and lower epidermal cells which were irregular, mostly tetragonal. Epidermis was amphistomatic while stomata were found as anisocytic (Paracytic). Trichomes were sessile or stalked stellate, three to five rayed and secondarily branched. Pollen grains were free, medium-sized or small, radially symmetrical, tricolporate, apolar, spherical or prolate spheroidal in shape.